Applicability of Antibody and mRNA Expression Microarrays for Identifying Diagnostic and Progression Markers of Early and Late Stage Colorectal Cancer. Issue 1 (2nd June 2013) - Spisák, Sándor; Galamb, Barnabás; Sipos, Ferenc; Galamb, Orsolya; Wichmann, Barnabás; Solymosi, Norbert; Nemes, Balázs; Molnár, Jeannette; Tulassay, Zsolt; Molnár, Béla
Abstract : The exact molecular background and the connection between protein and mRNA expression in colorectal cancer (CRC) development and progression are not completely elucidated. Our purposes were the identification of protein markers of colorectal carcinogenesis and progression using protein arrays and validation on tissue microarrays. The connection between antibody and mRNA expression array results was also examined. Using cancerous and adjacent normal samples from 10 patients with early and 6 with advanced CRC, 67 differentially expressed genes were identified between normal and cancerous samples. A marker set containing 6 proteins (CCNA1, AR, TOP1, TGFB, HSP60, ERK1) was developed which could differentiate normal specimen, early and late stage CRC with high sensitivity and specificity. Dukes D stage samples were analyzed on HGU133plus2.0 microarrays. In these samples, mRNA and protein expression of 143 genes showed strong positive correlations ( R 2 > 0.8), while a negative correlation ( R 2 > 0.9) was found in case of 95 genes. Based on our results a correlation could be established between transcriptome and antibody array results, hence the former may be used as a high-capacity screening method before applying antibody arrays containing already planned targets. Antibody microarrays may have a fundamental importance in testing of marker combinations and future application in diagnostics of tumorous diseases.